2012
DOI: 10.1002/nbm.2840
|View full text |Cite
|
Sign up to set email alerts
|

High‐precision calibration of MRS thermometry using validated temperature standards: effects of ionic strength and protein content on the calibration

Abstract: Currently, there is very limited ability to measure the temperature of the brain, but a direct technique for its estimation in vivo could improve the detection of patients at risk of temperature-related brain damage, help in the diagnosis of stroke and tumour, and provide useful information on the mechanisms of thermoregulation of the brain. In this article, new calibrations in vitro of MRS thermometry using temperature-stabilised reference phantoms are reported. The phantoms comprise two concentric glass sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…In common with all MRS studies of brain temperature in human subjects the accuracy of the measurement remains unverified, as it is dependent upon the calibration factors used for which there is considerable variation in published values and a known dependence on acquisition and analysis methods. Of the published calibrations, similar values for the temperature dependence of Δ H2O-NAA have been reported in four studies (Kuroda et al, 2003; Prakash et al, 2014; Vescovo et al, 2013; Zhu et al, 2008) and therefore this study has used these values while modifying the intercept values to obtain the same assumed mean WM temperature from all three reference measurements.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In common with all MRS studies of brain temperature in human subjects the accuracy of the measurement remains unverified, as it is dependent upon the calibration factors used for which there is considerable variation in published values and a known dependence on acquisition and analysis methods. Of the published calibrations, similar values for the temperature dependence of Δ H2O-NAA have been reported in four studies (Kuroda et al, 2003; Prakash et al, 2014; Vescovo et al, 2013; Zhu et al, 2008) and therefore this study has used these values while modifying the intercept values to obtain the same assumed mean WM temperature from all three reference measurements.…”
Section: Discussionmentioning
confidence: 76%
“…Several reports have published calibration values based on measurements in phantoms (Cady et al, 1995; Corbett et al, 1995; Covaciu et al, 2010), rat brain (Zhu et al, 2008) and piglet brain (Cady et al, 1995; Cady et al, 2010), however, with little agreement on the calibration values. It has been demonstrated that calibrations in solutions depend on protein and ionic content (Vescovo et al, 2013) and that the spectral fitting (Zhu et al, 2008) and data acquisition (Childs et al, 2007; Prakash et al, 2014) methods can affect the results. The in vivo calibration measurements will additionally be affected by the magnetic susceptibility of the sampled tissue region, which has previously not been taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Six pH normalized, pH ~ 7, solutions were studied, using N ‐acetylaspartate (NAA) (25 mM ) as the reference metabolite (see Table later), with four out of the six solutions identical to those used in the study by Vescovo et al to allow investigation of the effect of magnetic field strength on the calibration curve. A control solution and varied NaCl/KCl concentrations, used to approximate the ionic concentrations of neuronal and glial cells , facilitated the investigation of the ionic concentration effect on the temperature calibration (see Table later).…”
Section: Methodsmentioning
confidence: 99%
“…The fixed‐point organic compounds were ethylene carbonate and diphenyl ether, freezing at 35.8 °C and 26.3 °C, respectively. The procedure used to attain a stable temperature with the frozen organic compounds has been described in detail previously . In brief, the organic temperature reference phantoms were heated in a water bath (70 °C) for 1 h then transferred to a cool water bath (20 °C) and left to super‐cool (1 h).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the difficulties of direct monitoring of temperature (or any other parameter) deep inside the head, our understanding of cerebral homeothermy of the healthy human brain has been rather limited. However, in recent years, noninvasive, magnetic resonance spectroscopy ( 1 HMRS) and imaging 1 HMRSI techniques have been developed, allowing internal temperature to be measured in healthy adults [3,4]. Results show that small differences only exist between the brain and deep body temperature [5,6].…”
Section: Introductionmentioning
confidence: 98%